Pencil Back-Projection Method for SAR Imaging - Ozsoy, Sahin; Ergin, A. Arif (IEEE-Inst Electrical Electronics Engineers Inc, 2009)
We present a high-resolution method for spotlight mode SAR imaging that utilizes parametric modeling of projected target reflectivity density function and tomographic reconstruction. The method requires no polar-to-cartesian interpolation in spectral domain. Utilization of forward-backward total least squares bandpass matrix pencil method allows super resolution to be achieved in range for a single imaging angle. Hence, the quality of the image reconstructed by convolution back-projection is also improved. It is shown that the method is very resistant to noise and can generate images down to very low SNR values. Direct formulation in terms of physical quantities such as electric field and current density is another contribution of this paper.
Keywords: Convolution back projection (CBP); matrix pencil (MP); synthetic aperture radar (SAR); tomographic radar imaging